EXECUTIVE FUNCTION; PENINGKATAN MINAT BELAJAR SISWA BERBASIS MULTIPLE INTELEGENCE - Yulia Siska; Ambyah Harjanto (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This paper aims to describe the study of literature on executive function and its effect on increasing the interest in learning of elementary school students in terms of multiple intelligences. The method used is a literature review sourced from articles, journals, and reference books related to executive functions, interest in learning, and multiple intelligence. From the results of the study, it was found that there are four psychological factors that can increase student interest in learning situations in the classroom. The four psychological factors are involvement, convenience, clarity, and specifics. Involvement requires students to feel involved in class activities to attend to specific characteristics of the subject matter.